Investigating the role of human frontal eye field in the pupil light reflex modulation by saccade planning and working memory - Hsu, Tzu-Yu; Wang, Hsin-Yi; Chen, Jui-Tai; Wang, Chin-An (Frontiers in Human Neuroscience, 2022)
The pupil constricts in response to an increase in global luminance level, commonly referred to as the pupil light reflex. Recent research has shown that these reflex responses are modulated by high-level cognition. There is larger pupil constriction evoked by a bright stimulus when the stimulus location spatially overlaps with the locus of attention, and these effects have been extended to saccade planning and working memory (here referred to as pupil local-luminance modulation). Although research in monkeys has further elucidated a central role of the frontal eye field (FEF) and superior colliculus in the pupil local-luminance modulation, their roles remain to be established in humans. Through applying continuous theta-burst transcranial magnetic stimulation over the right FEF (and vertex) to inhibit its activity, we investigated the role of the FEF in human pupil local-luminance responses. Pupil light reflex responses were transiently evoked by a bright patch stimulus presented during the delay period in the visual- and memory-delay tasks. In the visual-delay task, larger pupil constriction was observed when the patch location was spatially aligned with the target location in both stimulation conditions. More interestingly, after FEF stimulation, larger pupil constriction was obtained when the patch was presented in the contralateral, compared to the ipsilateral visual field of the stimulation. In contrast, FEF stimulation effects were absence in the memory-delay task. Linear mixed model results further found that stimulation condition, patch location consistency, and visual field significantly modulated observed pupil constriction responses. Together, our results constitute the first evidence of FEF modulation in human pupil local-luminance responses.